In Vitro Multiplication of Photinia (Photinia X Fraseri)Usingdifferent Culture Media - Mohammed AL-Mizory, Layla Sh.; Hassan, Ameena M. (Science Journal of University of Zakho, 2014)
A very high rate of multiple shoots was obtained from nodal explants of Photinia x fraseri on MS medium supplemented with a various concentration of Kin alone (1, 2, and 3) mgl-1alone and combination of Kin at (1, 2, and 3) mgl-1 with IBA or IAA at (0.2 and 0.4) mgl-1. The results show that the number of shoots/ explant was significantly affected the levels of Kin alone and combination with IBA or IAA. The number of shoots (6.00 shoot/ explant) when Kin added to the medium at 3mgl-1 in which it was significantly different from other Kin concentrations. While the effect of different medium with the fixed and best concentration of Kin+ IBA and Kin+ IAA on the average shoot number and leaves number /explant of Photinia explant (node segment and shoot tips) The highest number of shoots (5.90) was recorded in node segment when cultured on WPM containing Kin+ IBA and it was increased significantly compared with all treatments from shoot tip. However, the maximum number of leaves (20.10) was recorded on WPM medium supplemented with Kin+ IBA and it was increased significantly compared with all treatments which containing different media plus Kin at 2mgl-1 + 0.4mgl-1 IBA and Kin at 1mgl-1+ 0.4mgl-1 IAA.Shootlel form the combination of from photinia cultured on ¼MS medium improved 0.6 mgl-1NAA concentration produced the highest number of roots/shootlel (6.5roots/shootlet) compared with all treatments contains ½MS medium added IAA, IBA and NAA on all concentration. While, theshootlets from photinia cultured on ¼MS medium and supplemented with 0.6mgl-1NAA formed an average (5.29 cm) compared to all treatments containing ½MS medium. Such plantlets were successfully transferred to soil after hardening with a high rate of survival.